The Impact of Dialogic Teaching on Alleviating Foreign Language Speaking Anxiety Among High-School Students - Insaf Khoudri (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2026)
Providing training for EFL learners to boost their communicative skills is a requirement in the 21st century. Instructors need to be actively engaged in adopting interactive teaching approaches instead of relying solely on the lecturing-based approach. Adopting a dialogic-based approach has demonstrated enhancement in students’ communication skills. This paper aims to investigate the impact of dialogic teaching on EFL learners’ levels of anxiety. To achieve this purpose, a quantitative research approach was adopted. A questionnaire was developed based on the readings of the literature and administered to 150 high school students in Morocco. Based on the results, the dialogic teaching approach proved to be successful in enhancing students’ communicative skills. Furthermore, the majority of the participants expressed their anxiety-free while making mistakes, enjoying their language class, and low anxiety when they spoke to natives. Additionally, the relationship between students and the students-teacher relationship boosted their freedom of expression. Through this approach, students’ non-linguistic skills, including self-confidence, teamwork, and stress management, were developed. This research paper implies that the effectiveness of this approach may vary among learners, possibly due to individual differences, such as their mindsets.